Extraversion and agreeableness: Divergent routes to daily satisfaction with social relationships - TOV, William (Institutional Knowledge at Singapore Management University, 2016)
We examined the unique effects of extraversion and agreeableness (and honesty-humility) on everyday satisfaction with family, friends, romantic life, and acquaintances, and explored potential mediators of these effects. Three diary studies (Ns = 206, 139, 185) were conducted on Singaporean university students. In Studies 1 and 2, participants rated their satisfaction with different relationship categories. In Study 3, participants rated their satisfaction and social interactions with 10 target individuals each day for a 1-week period. Both extraversion and agreeableness predicted relationship satisfaction. However, the effect of extraversion was mediated by greater levels of trust in others, whereas the effect of agreeableness was mediated by less frequent negative exchanges (e.g., criticism, perceived anger, and perceived neglect). The effect of honesty-humility on negative exchanges was similar to agreeableness. When both were entered as predictors, only the effect of honesty-humility was significant. We discuss how the processes by which personality affect relationship satisfaction vary depending on the trait as well as the particular measure that is used (IPIP NEO PI-R, California Q-Set, and IPIP-HEXACO).